Guanine Substitutions Prevent Conformational Switch from Antiparallel to Parallel G-Quadruplex - Bednářová, Klára; Kejnovská, Iva; Vorlíčková, Michaela; Renčiuk, Daniel (Chemistry (Weinheim an der Bergstrasse, Germany), 2019)
Guanine quadruplexes, recently reported to form in vivo, represent a broad spectrum of non-canonical conformations of nucleic acids. The actual conformation might differ between water solutions and crowding or dehydrating solutions that better reflect the conditions in the cell. Here we show, using spectroscopic techniques, that most guanine substitutions prevent the conformational switch from antiparallel or hybrid forms to parallel ones when induced by dehydrating agents. The inhibitory effect does not depend on the position of the substitution, but, interestingly, on the type of substitution and, to some extent, on its destabilising potential. A parallel form might be induced in some cases by ligands such as N-methyl mesoporphyrin IX and even this ligand-induced switch is inhibited by guanine substitution. The ability or inability to have a conformation switch, based on actual conditions, might significantly influence potential conformation-dependent quadruplex interactions.
Keywords: DNA structures; modified nucleobases; G-quadruplexes; dehydrating environment; circular dichroism